Enlightened Regulatory Capture - Thaw, David (2014)
Regulatory capture generally evokes negative images of private interests exerting excessive influence on government action to advance their own agendas at the expense of the public interest. There are some cases, however, where this conventional wisdom is exactly backwards. This Article explores the first verifiable case, taken from healthcare cybersecurity, where regulatory capture enabled regulators to harness private expertise to advance exclusively public goals. Comparing this example to other attempts at harnessing industry expertise reveals a set of characteristics under which regulatory capture can be used in the public interest: (1) legislatively mandated adoption of recommendations by an advisory committee comprising private interests and “reduced-bias” subject matter experts; (2) relaxed procedural constraints for committee action to prevent internal committee capture; and (3) opportunities for committee participation to be worthwhile for representatives of private parties beyond the mere opportunity to advance their own interests. This Article presents recommendations based on those characteristics as to how and when legislatures may endeavor to replicate this success in other industries to improve both the legitimacy and efficacy of the regulatory process